Land, protest, and politics : the landless movement and the struggle for agrarian reform in Brazil - Ondetti, Gabriel A. (University Park, Pa. : Pennsylvania State University Press, 2008)
"Analyzes the development of the movement for agrarian reform in Brazil, and attempts to explain the major moments of change in its growth trajectory, from the late 1970s to 2006"--Provided by publisher.
Includes bibliographical references (p. [249]-267) and index.
Keywords: Movimento dos Trabalhadores Rurais sem Terra (Brazil); Land reform -- Brazil; Agricultural laborers -- Political activity -- Brazil